Thermoelectric studies of electronic properties of ferromagnetic GaMnAs layers - Osinniy, V.; Dybko, K.; Jedrzejczak, A.; Arciszewska, M.; Dobrowolski, W.; Story, T.; Radchenko, M.V.; Sichkovskiy, V.I.; Lashkarev, G.V.; Olsthoorn, S.M.; Sadowski, J. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
Thermoelectric power, electrical conductivity, and high field Hall effect were studied over a broad temperature range in ferromagnetic Ga₁₋xMnxAs epitaxial layers (0.015 ≤ x ≤ 0.06). Thermoelectric power analysis gives information about carrier transport mechanisms in layers with both metallic and non-metallic types of conductivity and allows determination of the Fermi energy and carrier concentration. At high temperatures (T > 70 K), the thermoelectric power in GaMnAs linearly increases with increasing temperature. That indicates the presence of a degenerate hole gas with the Fermi energy EF = 220 ± 25 meV, nearly independent of Mn content (for 0.02 ≤ x ≤ 0.05). At lower temperatures, GaMnAs layers with metallic-type conductivity show an additional contribution to the thermoelectric power with the maximum close to the Curie temperature.